Molecular Insights Into Withaferin-A-Induced Senescence: Bioinformatics and Experimental Evidence to the Role of NFκB and CARF. (28th April 2018) - Bhargava, Priyanshu; Malik, Vidhi; Liu, Ye; Ryu, Jihoon; Kaul, Sunil C; Sundar, Durai; Wadhwa, Renu
Abstract: Withaferin-A (Wi-A) has been shown to possess anticancer activity. Molecular mechanism(s) of its action has not been fully resolved. We recruited low dose of Wi-A that caused slow growth arrest in cancer cells and was relatively safe for normal cells. Consistently, we detected nuclear translocation of nuclear factor kappa B (NFκB) and activation of p38MAPK selectively in cancer cells. Bioinformatics analyses revealed that Wi-A did not disrupt IKKα/IKKβ–Nemo complex that regulates NFκB activity. However, it caused moderate change in the conformation of IKKβ–Nemo interacting domain. Experimental data revealed increased level of phosphorylated IκBα in Wi-A-treated cells, suggesting an activation of IKK complex that was supported by nuclear translocation of NFκB. Molecular docking analysis showed that Wi-A did not disrupt; however, decreased the stability of the NFκB–DNA complex. It was supported by downregulation of DNA-binding and transcriptional activities of NFκB. Further analysis revealed that Wi-A caused upregulation of CARF (collaborator of ARF) demonstrating an activation of DNA damage oxidative stress response in both cancer and normal cells. In line with this, upregulation of p21 WAF1, p16 INK4A, and hypophosphorylated pRB and induction of senescence were observed demonstrating that Wi-A-induced senescence is mediated by multiple pathways in which CARF-mediated DNA damage and oxidative stress play a major role.